Diversity Unlocks Creativity and Innovation. (1st March 2022) - Badilescu, Simona; Packirisamy, Muthukumaran
Abstract : A research lab where international students are working toward their PhD and Master's degrees along with senior researchers is like a unit cell in the body of the university. What better model can be available for analyzing the success of research by providing a supportive and inclusive work environment that welcomes and encourages students, coming from a diversity of countries, languages, religious and socioeconomic backgrounds? This paper presents the mechanism that was instrumental in making the women researchers as well as the international students feel comfortable and helped them to explore and contribute to the multidisciplinary aspects of our lab.We highlight the important milestones in our lab work environment over the last fifteen years, with a focus on diversity, and we stress the beneficial role of the direction of the lab and the diversifying faculty in providing critically needed role models to our students. We emphasize the strength of diversity that unlocks imagination and intellectual curiosity. The paper includes stories showing the building of strong and creative lab culture.